Suboptimality with land - Kokonas, Nikos; Polemarchakis, Herakles (Research in Agricultural & Applied Economics, 2015)
In a stochastic economy of overlapping generations subject to uninsurable risks, competitive allocations need not be constrained optimal. This is the case even in the presence of long-lived assets and no short sales.